2012
DOI: 10.1111/fwb.12004
|View full text |Cite
|
Sign up to set email alerts
|

Higher temperature reduces the effects of litter quality on decomposition by aquatic fungi

Abstract: Summary 1. We investigated the effects of riparian plant diversity (species number and identity) and temperature on microbially mediated leaf decomposition by assessing fungal biodiversity, fungal reproduction and leaf mass loss. 2. Leaves of five riparian plant species were first immersed in a stream to allow microbial colonisation and were then exposed, alone or in all possible combinations, at 16 or 24 °C in laboratory microcosms. 3. Fungal biodiversity was reduced by temperature but was not affected by lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 53 publications
11
61
2
Order By: Relevance
“…Highest diversity in the present study was in the river habitat, with lowest salinity and temperature as observed previously for temperature (Fernandes et al 2012, Hyde et al 2016) and salinity (Shearer 1972, Tsui et al 2001, 2004, Fryar et al 2004, Pearman et al 2010, Richards et al 2012. However, a multitude of factors affect aquatic fungal diversity and a combination of these result in the diversity seen across habitats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Highest diversity in the present study was in the river habitat, with lowest salinity and temperature as observed previously for temperature (Fernandes et al 2012, Hyde et al 2016) and salinity (Shearer 1972, Tsui et al 2001, 2004, Fryar et al 2004, Pearman et al 2010, Richards et al 2012. However, a multitude of factors affect aquatic fungal diversity and a combination of these result in the diversity seen across habitats.…”
Section: Discussionsupporting
confidence: 86%
“…Aquatic hyphomycetes are adapted to lotic freshwater environments growing on dead plant material such as leaf litter (Ingold 1942, Medeiros et al 2009, Fernandes et al 2012) and submerged lignicolous material (Yuen et al 1998, Vijaykrishna et al 2006, Shearer et al 2007, Kuehn 2016. Sexual ascomycetes also display adaptations to aquatic environments (Willoughby & Archer 1973, Pearman et al 2010, and facilitate decomposition and softening of lignicolous wood substrates (Hyde et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In these environments, some authors (Fierer et al, 2005;Conant et al, 2008;Wetterstedt et al, 2010) have reported that low-quality material decomposition (structurally complex C substrates) appears to be more sensitive to temperature increase than high-quality ones, possibly because the microbial enzymatic reactions require a higher net activation energy to metabolise structurally complex C substrates (Bosatta & Å gren, 1999). This suggests that organic substrate quality would have a significant and predictable influence on the sensitivity of microbially mediated decomposition to temperature, which might also occur in freshwater ecosystems (Fernandes et al, 2012). However, whereas studies on individual effects of these two factors on litter processing are common in the literature, few studies have so far addressed the interaction between temperature and detritus quality and their implications on litter processing in freshwater ecosystems (see Ferreira & Chauvet, 2011a;Fernandes et al, 2012;Gonçalves et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in water temperature can accelerate the leaching of soluble compounds and favor microbial activity, positively influencing the leaf breakdown (Fernandes et al, 2012). However, we observed that urbanization (increase in electrical conductivity, water temperature, turbidity and NO 2 ; and decrease in dissolved oxygen) had a negative effect on the leaf breakdown of P. sellowii, probably due to the fact that these streams contain lower fungal biomass and no invertebrate shredders.…”
Section: Discussionmentioning
confidence: 62%